A Study of Natural Herbal Drugs for Cancer Chemoprevention: Exploring the Potential of Plant-Derived Compounds in Treating Cancer (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cancer is the second leading cause of death in the world, following heart disease and respiratory disease. A long way still needs to be gone in the treatment and control of cancer progression, despite great strides being made. Chemotherapy can have a number of unfavourable side effects. Adverse side effects may be reduced with natural therapies like the use of plant-derived cancer treatment products. Several plant products are currently being investigated as potential cancer treatments. Although many plant products have shown promising anti-cancer properties in vitro, human trials are still pending for many of these compounds. The effectiveness of these plant products in treating human cancer will require additional research. There have been numerous plant-derived chemical compounds developed recently that have shown promise as anticancer agents, and their potential mechanisms of action will be discussed in detail in this review.